Implementasi Standar Operasional Prosedur (SOP) oleh Leader dalam Menjaga Kualitas Produk Sepatu pada PT Masanda Jaya Brebes - Disiya Intan Setiyawati (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
Field Experience Practice (PPL) or internship is a practical course carried out directly in a company according to the student's field of study, with the aim of integrating lecture theory and real work practice. PPL is worth 6 credits and is a mandatory part of the curriculum for undergraduate students at the Putera Bangsa Tegal Islamic Economics College. Students who have not participated in PPL are not considered to have met the academic qualifications as graduates. This program aims to produce competent graduates as academics, researchers, consultants, accounting practitioners, and creative, innovative, and professional Muslim entrepreneurs. Through PPL, students are expected to improve their personal qualities, work experience, and understanding of the business world and development policies. The PPL implementation took place from September 14, 2025 to January 15, 2026 at PT Masanda Jaya. The Sharia Business Management Study Program views PPL as a strategic tool to understand management practices, SWOT analysis, governance, and company strategies in achieving organizational goals. The PPL report compiled by the author has the theme of the FAJAR internship.